NHLBI Step-by-Step Approach to Adapting Cardiovascular Training and Education Curricula for Diverse Audiences - Robinson Fulwood, PhD, MSPH; Madeleine F. Wallace, PhD, MS; Matilde Alvarado, MS, RN (Centers for Disease Control and Prevention, 2008)
Racial and ethnic minority communities need to be involved in developing health information to ensure its cultural appropriateness, improve its acceptability, and stimulate adoption of healthy behaviors. The National Heart, Lung, and Blood Institute at the National Institutes of Health adapted a heart-health curriculum for Latinos into culturally appropriate curricula for American Indians/Alaska Natives, African Americans, and Filipinos. Lessons learned from this process can assist public health practitioners interested in adapting science-based heart-health information into practical health education messages that meet the cultural and contextual needs of diverse groups.